Intergenerational learning and cultural transmission in pandai sikek songket weaving: a qualitative case study in west sumatra, indonesia - Purwo Prihatin; Sunarmi Sunarmi; Andar Indra Sastra (Jurnal Konseling dan Pendidikan, 2025)
Studies on Pandai Sikek songket as Minangkabau cultural heritage have largely remained descriptive, focusing on its aesthetic, symbolic, and economic values, while offering limited analysis of the cultural transmission mechanisms that sustain weaving skills across generations. This study aims to examine intergenerational learning and social transmission of songket weaving skills in Nagari Pandai Sikek, Tanah Datar, West Sumatra, with particular emphasis on vertical, horizontal, and oblique transmission. This research employs a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews, and documentation involving ten purposively selected informants, including weavers, academics, traditional leaders, and representatives of the nagari government. Data analysis followed an interactive analytical model, and the credibility of the findings was ensured through triangulation of sources, techniques, and time.The findings indicate that vertical transmission occurs within the family through early-age learning, horizontal transmission takes place through peer interactions and collective practices, and oblique transmission is mediated by actors and institutions beyond kinship relations. These results highlight that Pandai Sikek songket functions not only as a technical craft but also as a medium of social learning that plays a crucial role in sustaining educational, social, and religious values within Minangkabau society.